2018
DOI: 10.3389/fnins.2018.00686
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Familiarity in Music Listening: A Systematic Review and a Neuroimaging Meta-Analysis

Abstract: Familiarity in music has been reported as an important factor modulating emotional and hedonic responses in the brain. Familiarity and repetition may increase the liking of a piece of music, thus inducing positive emotions. Neuroimaging studies have focused on identifying the brain regions involved in the processing of familiar and unfamiliar musical stimuli. However, the use of different modalities and experimental designs has led to discrepant results and it is not clear which areas of the brain are most rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 89 publications
(127 reference statements)
5
57
3
Order By: Relevance
“…The left hippocampus, present in the key network in this study, has been found to be related to retrieval success for music memory (Gagnepain et al, 2017;Watanabe, Yagishita, & Kikyo, 2008) and to be involved in coding expectancy violations that are caused by reward anticipation (Gebauer et al, 2012;Salimpoor, Zald, Zatorre, Dagher, & McIntosh, 2015). The left hippocampus and temporal pole have been found to be active in familiar music listening contrasted to non-familiar music listening (Freitas et al, 2018;Pereira et al, 2011;Plailly et al, 2007).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…The left hippocampus, present in the key network in this study, has been found to be related to retrieval success for music memory (Gagnepain et al, 2017;Watanabe, Yagishita, & Kikyo, 2008) and to be involved in coding expectancy violations that are caused by reward anticipation (Gebauer et al, 2012;Salimpoor, Zald, Zatorre, Dagher, & McIntosh, 2015). The left hippocampus and temporal pole have been found to be active in familiar music listening contrasted to non-familiar music listening (Freitas et al, 2018;Pereira et al, 2011;Plailly et al, 2007).…”
Section: Discussionmentioning
confidence: 57%
“…The amygdala is a crucial hub involved in many network configurations, and has been implicated in functions ranging from establishing valence or salience, cognition, reward, and social learning (Rutishauser, Mamelak, & Adolphs, 2015). Amygdala activations have previously been found in emotional responses to musical stimuli, namely in listening to familiar music (Freitas et al, 2018;Koelsch, Fritz, v. Cramon, MĂŒller, & Friederici, 2006;Pereira et al, 2011), and in violation of musical expectancies (Gebauer et al, 2012;Koelsch, Fritz, & Schlaug, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important literature exists concerning the exploration of musical cognition [18,[70][71][72][73][74] with neuroimaging methods. However, experimental works specifically focusing on musical memory are much scarcer [75][76][77] and mainly done in healthy subjects. We emphasize the complementary results of four neuroimaging studies allowing assumptions on the underlying cerebral substrates organization of episodic and semantic memories and verbal and musical memories and their dissociations.…”
Section: Contribution Of Neuroimaging Resultsmentioning
confidence: 99%
“…For example, in both monkeys and humans, learning to play sounds on a keyboard is subsequently associated with specific activation of sensorimotor regions involved in making finger and hand movements when listening to those sounds [80][81][82][83][84][85] . More generally, musical training improves sound and speech perception and these improvements are typically associated with sensorimotor regions [85][86][87][88][89][90] . Similarly, learning new speech sounds, novel words and artificial languages are all associated with more sensorimotor activity during perception following learning and consolidation 79,[91][92][93][94][95][96][97][98][99] .…”
Section: Speech Perceptionmentioning
confidence: 99%